Reducing ammonia loss from urea by mixing with humic and fulvic acids isolated from coal - Abdul Reeza, Ameera; Ahmed, Osumanu Haruna; Nik Ab. Majid, Nik Muhamad; Jalloh, Mohamadu Boyie (Science Publications, 2009)
Problem statement: Ammonia volatilization is a major pathway for nitrogen loss from surface applied urea. While all top-dressed ammonia and ammonium based N fertilizers can volatilize, the potential loss is greatest with urea and fluids containing urea. As much as 20-50% of N applied to soils is lost through volatilization alone. Thus, the objective of this laboratory study was to reduce ammonia loss from urea via mixing with humic and fulvic acids isolated from coal. Approach: This study compared four different types of treatments which were urea without additives (T1), urea with humic acid-powdered form (T2), urea with fulvic acid-liquid form (T3) and urea with humic and fulvic acids-liquid form (T4). Comparisons were made based on ammonia loss, soil NH4 and NO3- contents as well as exchangeable cations in the treated soils. Soil samples from typic paleudults (Bekenu series) were used. Humic substances were isolated using standard procedures. Daily ammonia loss from soil was measured using a modified closed-dynamic air flow system method. Results: All of the treatments with humic substances significantly reduced ammonia loss ranging between 13 and 25% compared to urea alone. The treatment with both humic and fulvic acids (T4) showed pronounced ammonia loss reduction. All treatments with humic substances significantly increased NH4+ and NO3- content in soil samples compared to urea alone except for treatment having humic acid alone (T2). Treatments with fulvic acid (T3 and T4) also showed significant increase in exchangeable K+ and Na+ compared to urea alone. The increase in the formation of NH4+ over NH3, soil exchangeable cations and temporary reduction of soil pH may had retarded urea hydrolysis in the immediate vicinity of the fertilizer. Conclusion: Surface applied urea fertilizer efficiency could be increased if applied together with humic and fulvic acids.